Immunomodulation of FOXP3+ regulatory T cells by the aromatase inhibitor letrozole in breast cancer patients. - Generali, D; Bates, G; Berruti, A; Brizzi, M; Campo, L; Bonardi, S; Bersiga, A; Allevi, G; Milani, M; Aguggini, S; Dogliotti, L; Banham, A; et al. (2009)
PURPOSE: We have shown previously that tumor infiltration by FOXP3+ regulatory T cells (Treg) is associated with increased relapse and shorter survival of patients with both in situ and invasive breast cancer. Because estrogen regulates Treg numbers in mice and promotes the proliferation of human Tregs, we hypothesized that blocking estrogen receptor-alpha signaling would abrogate Tregs and be associated with response to hormonal therapy and increased survival. EXPERIMENTAL DESIGN: FOXP3+ Tregs were quantified in tumor samples collected at baseline by incisional biopsy and after 6 months at definitive surgery in 83 elderly breast cancer patients (T2-4 N0-1) enrolled in a randomized phase II trial based on 6 months of primary letrozole (2.5 mg/d) or 6 months of letrozole plus oral "metronomic" cyclophosphamide (50 mg/d). RESULTS: Treg number ranged from 0 to 380 (median, 30) before treatment and from 0 to 300 (median, 8) after treatment. There was a significant reduction in Tregs in letrozole and letrozole-cyclophosphamide patients (P < 0.0001 and P < 0.002, respectively) after treatment. Treg number at residual histology was inversely related with response (P < 0.03 and P = 0.50, respectively) and a greater Treg reduction was observed in responding patients (P < 0.03). CONCLUSION: This study suggests that aromatase inhibitors may have an indirect antitumor mechanism of action through reducing Tregs in breast tumors and may be of use in estrogen receptor-alpha-negative tumors in combination with immunotherapy approaches.